ANALYSIS OF RHYTMIC LEARNING IN FOURTH GRADE ELEMENTARY CLASSROOMS - Erin Khoerunisa; Resa Respati; Rosarina Giyartini (STKIP Subang, 2025)
This study aims to analyze rhythmic learning in fourth-grade elementary school classes, including its implementation, the obstacles encountered, and alternative solutions to improve its effectiveness. The background of this research is based on the fact that rhythm is a fundamental aspect of music education, playing a vital role in developing students’ concentration, motor coordination, discipline, and collaborative skills. Nevertheless, rhythmic learning practices in elementary schools still face various challenges, including teachers’ limited competence in music, a lack of diverse teaching methods, and insufficient supporting learning media. This research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation studies involving teachers and fourth-grade elementary students. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings revealed that rhythmic learning in fourth grade is largely implemented through lectures and repetitive drills, with little engaging variation. The main obstacles identified include teachers’ difficulties in explaining rhythmic notation concepts, the limited availability of simple musical instruments, and students’ low motivation to participate actively. Based on these findings, alternative solutions are required, such as the application of more contextual and enjoyable learning methods for example, game-based approaches, body percussion, or the Orff method, which integrates music, movement, and collaborative activities. Such approaches are considered effective in enhancing students’ engagement, rhythmic concept comprehension, and interest in music learning. In conclusion, this analysis provides an important contribution to the development of rhythmic learning strategies in elementary schools, making them more effective, creative, and meaningful.